Sex Talks Between LGBTQ+ Parents and Children - (:unkn) unknown (My University, 2022)
Research on parent-child sex talks typically focuses on the perspectives of heterosexual parents. The reported number of queer parents is growing in the United States (Baker, 2019), and thus more children are hearing about sex topics from the points of view of sexual minorities. Thus, including queer perspectives on a topic that can have a lot of influence on sexual behaviors is imperative. The purpose of this research is to understand topics that are covered in sex topic conversations between LGBTQ+ parents and their children, how LGBTQ+ parents approach the conversations, and what LGBTQ+ parents’ goals are for the conversations. I conducted semi-structured interviews with 15 LGBTQ+ parents, and I analyzed the interview data using Braun and Clarke’s (2006, 2022) six-step thematic analysis. Themes related to what topics parents cover include: Consent as a Foundational Knowledge, Pleasure is Okay, but Private, Heteronormativity and the Nuclear Family as not the Only Option, and Information Outside Personal Sex Experiences. Themes regarding how parents approached these conversations include approaching sex talks: as a Series of Events, as a Dialogue, as Age-Appropriate, with Supplementary or Complementary Materials, and as “Clinical.” The last four themes are related to the goals parents have for sex topic conversations: Doing Better Than Own Parents, Cultivating a Sense of Ownership, Being Open and Honest to Encourage Future Discussions, and Raising Informed, Educated, and Knowledgeable Children. LGBTQ+ parents do talk to their children about a variety of sex topics to keep them informed about complicated concepts related to sex, to help them feel comfortable in their own bodies, and to prepare them for future sexual encounters. Implications for this research include emphasizing the importance of producing inclusive sex education material and the lasting impact these conversations can have on the children and their futures as parents themselves. Limitations and future directions, including finding diverse, intersectional perspectives and understanding experiences of children of LGBTQ+ parents are also discussed.
Keywords: LGBTQ+ parenting; parent-child communication; queer parenting; sex education; sex talks